The Evolution and Functioning of the EU Science for Policy Ecosystem (BioLaw Journal - Rivista di BioDiritto, 2026)
Scientific advice to policymaking plays a central role in modern techno-scientific societies, both informing and legitimizing policymaking. Yet a fundamental tension exists between its appeal to scientific authority and the need for policy relevance and democratic accountability. These concerns are particularly prominent in the context of European Union (EU) policymaking, in which scientific expertise and advice play a central role due to the technical nature of many EU policies. This paper traces the historical development of scientific advice in EU policymaking from the late 1990s to the most recent developments, zooming in on the functioning of the European Commission’s Scientific Advice Mechanism (SAM).
Keywords: scientific advice; science advice; European Union; European Commission; science for policy